Aged for Death (A Tuscan Vineyard Cozy Mystery-Book 2) - Fiona, Grace (Lukeman Literary, 2020)
"Very entertaining. I highly recommend this book to the permanent library of any reader that appreciates a very well written mystery, with some twists and an intelligent plot. You will not be disappointed. Excellent way to spend a cold weekend!" --Books and Movie Reviews, Roberto Mattos (regarding Murder in the Manor) AGED FOR DEATH (A TUSCAN VINEYARD COZY MYSTERY) is book #2 in a charming new cozy mystery series by #1 bestselling author Fiona Grace, author of Murder in the Manor (Book #1), a #1 Bestseller with over 100 five-star reviews-and a free download! Olivia Glass, 34, turns her back on her life as a high-powered executive in Chicago and relocates to Tuscany, determined to start a new, simpler life-and to grow her own vineyard. Olivia is falling in love with the Tuscan life and the gorgeous Tuscan scenery, especially as she travels to visit Pisa. Yet when the winery she works for auctions off a rare and expensive bottle of wine-and when someone turns up dead-Olivia must draw on her strength as a sommelier to get to the bottom of the murder. In the meanwhile, her new own attempts at a vineyard-and her love life-are failing miserably. Can Olivia turn it all around to create the life she's always dreamed of? Or was it all a fantasy that she should let go? Hilarious, packed with travel, food, wine, twists and turns, romance and her newfound animal friend-and centering around a baffling small-town murder that Olivia must solve-AGED FOR DEATH is an un-putdownable cozy that will keep you laughing late into the night. Book #3 in the series-AGED FOR MAYHEM-is now also available!
Keywords: Krimi, detektivky